The Utilization Of Counseling Flipchart At Integrated Health Post - Putriatri Krimasusini Senudin; Eufrasia Prinata Padeng; Eugenius Rada Masri; Yuliana Suryati (Jurnal Kesehatan Prima, 2020)
Integrated health post  is one form of community-based health efforts, which empowers and facilitates the community in obtaining basic health services, to accelerate the reduction in maternal and infant mortality. The Integrated health post  is ideally carried out with a five table system and five basic activities. Integrated health post  in local government clinic kota Ruteng has conducted registration, weighing and filling the Health Towards Card  (KMS) well, but the extension activity was never carried out by kader. Kader often find it difficult, because there is a lack of confidence and are not sure they are able to do counseling, especially for kader who have not attended extension training. In addition, the unavailability of standardized aids to be used when counseling at the Integrated health post . This research was conducted with an observational method with a cross sectional approach followed by 54 kader. Sampling using purposive sampling. The research instruments used were questionnaire and observation sheet. The results showed that the characteristics of respondents based on age were mostly more than 35 years old (51.9%), most had high school education background (70.4%), most of them had been kader  for 1-5 years (53.7% ) and most of them have never attended counseling training (63%).The use of flipcharts by the kader at the time of counseling in  Integrated health post   at the table four was good (51.8%). There is no relationship of age (0.022) and counseling training that has ever been followed (0.285) with the use of Integrated health post  training flipcharts. There is an educational relationship (0,000) and a long time as a kader  (0.001) with the use of counseling flipchart at Integrated health post . It can be concluded that flipchart can help kader  in conducting extension activities at table four  Integrated health post  balita in accordance with the problems and needs of participants.